2001
DOI: 10.4049/jimmunol.166.4.2167
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Peripheral Neuropeptides Attract Immature and Arrest Mature Blood-Derived Dendritic Cells

Abstract: Dendritic cells (DC) are highly motile and play a key role in mediating immune responses in various tissues and lymphatic organs. We investigated locomotion of mononuclear cell-derived DC at different maturation stages toward gradients of sensory neuropeptides in vitro. Calcitonin gene-related peptide, vasoactive intestinal polypeptide, secretin, and secretoneurin induced immature DC chemotaxis comparable to the potency of RANTES, whereas substance P and macrophage-inflammatory protein-3beta stimulated immatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
82
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(87 citation statements)
references
References 31 publications
4
82
0
1
Order By: Relevance
“…Hence, we wondered whether FTY720 might modulate chemokine receptor-driven DC migration. DC were allowed to migrate into nitrocellulose filters using RANTES and SDF-1a as stimulators [23]. Immature FTY720-and Comparative flow cytometric analysis of FTY720-treated DC, FTY720-P-treated DC and control DC.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, we wondered whether FTY720 might modulate chemokine receptor-driven DC migration. DC were allowed to migrate into nitrocellulose filters using RANTES and SDF-1a as stimulators [23]. Immature FTY720-and Comparative flow cytometric analysis of FTY720-treated DC, FTY720-P-treated DC and control DC.…”
Section: Resultsmentioning
confidence: 99%
“…First-strand cDNA was synthesized from 1 g of total RNA using a mixture of oligo(dT) [12][13][14][15][16][17][18] and random hexamer primers and Superscript Reverse Transcriptase (Invitrogen Life Technologies). For amplification, the qPCR Mastermix Plus for SYBR Green I without UNG (Eurogentec) was used to detect accumulation of PCR products during cycling on an Applied Biosystems 7300 cycler.…”
Section: Analysis Of Cytokine Mrna and Protein Productionmentioning
confidence: 99%
“…Importantly, CGRP also mediates distinct anti-inflammatory and immunosuppressive activities and, therefore, may play a role in neuroimmunological communication. CGRP modulates the adhesion and migration of immune cells including T cells, eosinophilic granulocytes, and dendritic cells (DC) (15)(16)(17). Stimulation of DC with CGRP reduces the expression of MHC class II and costimulatory proteins, augments the production of IL-10, and inhibits the Ag-presenting capacity of these cells (18 -20).…”
mentioning
confidence: 99%
“…Studies have shown that binding of neuropeptides to specific seven transmembrane domain G protein-coupled receptors expressed in various types of immune cells can activate or suppress different immune functions such as cytokine production (3), dendritic cell (DC) 4 maturation (4), Th2 cell polarization (5), and chemotaxis (6,7). These features and their implication in several inflammatory and autoimmune diseases have led to the development of receptorselective agonist and antagonist for the treatment of several diseases (8).…”
mentioning
confidence: 99%